Case Report: Subconjunctival Triamcinolone Acetate–associated Scleral Necrosis: Is It Really Obsolete?. Issue 9 (25th September 2021) - Agarwal, Rinky; Bafna, Rahul Kumar; Chetan, Chetan; Sharma, Namrata
Abstract : SIGNIFICANCE: Recent studies have established the safety of subconjunctival steroids for anterior scleritis, refuting scleral necrosis as a potential complication. However, presently, we report a rare case of scleral necrosis associated with subconjunctival triamcinolone acetate. PURPOSE: The purpose of this study was to report a case of scleral necrosis after subconjunctival triamcinolone acetate administration for nonresponsive anterior nodular scleritis. CASE REPORT: A 45-year-old man diagnosed with nodular anterior scleritis was administered subconjunctival triamcinolone acetate (4 mg) adjacent to the nodule after noting nonresponse for 4 months. Worsening of congestion was noted 3 weeks after the injection. Slit-lamp examination revealed diffuse congestion, 10 clock hours of anterior scleral necrosis, superior whitish depot of subconjunctival triamcinolone acetate, anterior segment flare, and few posterior synechiae. Ultrasound biomicroscopic imaging and contrast-enhanced computerized tomography showed a localized outpouching of sclera and buckling of anterior scleral wall superiorly. The result of the comprehensive blood profile and systemic evaluation undertaken to rule out any underlying autoimmune disorders and herpes zoster ophthalmicus was found negative. A diagnosis of subconjunctival triamcinolone acetate–associated scleral necrosis was made, and the patient was managed conservatively. Gradual improvement with dissolution of subconjunctival triamcinolone acetate and no recurrences till 2 years of follow-up were noted. CONCLUSIONS: Scleral necrosis is a potential complication of subconjunctival triamcinolone acetate. Judicious and cautious use of subconjunctival triamcinolone acetate is advocated for nonresolving anterior scleritis.